The Impact of Banking Sector on Economic Growth: Empirical Analysis from Palestinian Economy - Zidan, Khaled; Jazar, Yazan Abu; Gharbiah, Majd Abu (International Journal of Economics and Financial Issues, 2020)
This study attempts to investigate the impact of the Palestinian banking sector on economic growth that was measured by the Gross Domestic Product (GDP) during the period 2005-2017. The researcher chose bank’s credit as an explanatory variable which is measured by six independent variables namely Direct Credit Facilities (DCF), Indirect Credit Facilities (ICF), Loans to deposits (LTD), Deposits (DTGDP) Average Interest Rates (AIR) and Banks Investments in local financial securities (DTGDP). These variables are indicators of banking sector and affect the economic growth. The data was collected from the audited annual reports of the sample banks, the Palestinian Monetary Authority (PMA)’s annual reports and Association of Banks in Palestine. These variables had been used as a percentage of RGDP. The findings and analysis revealed that there is weak relationship between the economic growth and the banking sector.